Clustering as a Mechanism of Kazakhstan Agro-industrial Complex Economic Growth - ANOKHINA, Marina Y.; DARIBAYEVA, Elmira B.; JOLDASBAYEVA, Gulnar K. (Journal of Advanced Research in Law and Economics, 2019)
The purpose of the study is to develop the mechanism of clustering the agrarian economy of Kazakhstan as the basis for ensuring the economic growth of the agro-industrial complex (AIC) of the country. The methodology of the research is based on the author's concept of managing the economic growth of agro-industrial production and determining the role of clustering in ensuring its sustainability. In contrast to the previously developed approaches to the management of economic dynamics processes of the industrial complex, the identification of quantitative, qualitative and reproductive components is proposed. The influence of cluster technologies on reproductive dynamics of agro-industrial complex, the level of which determines opportunities and sustainability of economic growth of Kazakhstan agro-industrial production, is substantiated. The result of the research is the proposed algorithm of agrarian cluster establishment taking into account regional peculiarities of Kazakhstan, forming the basis of country agrarian economy clustering and ensuring the economic dynamics of agro-industrial production at a new qualitative level.